Success Of LMA Insertion Technique Using Opioid Free Anesthesia - Restika, Restika; Fendy Dwimartyono; Muhammad Asrul Apris (Jurnal EduHealth, 2024)
Airway management is one of the main focuses in anesthesia because patients under anesthesia are at risk for airway obstruction and aspiration. Airway management is essential for managing critically ill patients, trauma patients, and anesthesia, both during surgery and procedures outside the operating room. The Laryngeal Mask Airway (LMA) is a supraglottic airway device used to facilitate and ensure closure of the laryngeal cavity for spontaneous ventilation. Opioid-free anesthesia (OFA) is defined as an anesthetic technique in which opioids are not used in the perioperative period (systemic, neuraxial or intracavitary). There is a successful LMA insertion technique using opioid-free anesthesia.